DETERMINAN AUDIT DELAY DAN PERAN SPESIALISASI INDUSTRI AUDITOR SEBAGAI PEMODERASI - Monica, Agnes (Ma Chung Press, 2023)
The purpose of this study is to find empirical evidence regarding the effect of audit tenure, information asymmetry, financial distress, and the complexity of company operations on audit delay, as these effects will be moderated by industry specialization of auditors. This research was conducted at manufacturing companies listed on the Indonesia Stock Exchange in 2017 – 2021. This quantitative research used the documentation method as sampling. The sample for this study is 725 company data based on certain criteria. Data analysis using Moderated Regression Analysis (MRA). The results of this study indicate that the variable audit tenure and financial distress have a positive effect on audit delay, information asymmetry and the complexity of company operations have a negative effect on audit delay. the auditor industry is able to weaken the effect of information asymmetry and financial distress on audit delay. Meanwhile, this study contributes to supporting some explanations from agency theory on the audit delay phenomenon investigated. In addition, this research is also useful for the Public Accounting Firm (KAP) and company management in order to understand the triggering factors for audit delay.